Descrição sensorial de formulação de bolo sabor laranja isento de glúten - Castro, Geovana Teixeira de (2021)
Celiac disease (CD) is an autoimmune condition that manifests with gluten ingestion and affects the small intestine of genetically predisposed individuals. There is still no cure for CD, and the only viable treatment is permanent adherence to a gluten-free diet. However, gluten-free products are not always available in the markets and, when they are, there is no variety, the prices are higher, and a big nutritional deficiency is observed when compared to gluten-containing version. In order to make up for this nutritional lack, ingredientes can be added to enrich the formulation, as the teff, sorghum and yacon flours. The aim of this project was to sensorially describe glutenfree orange flavor cake formulations made with rice, sorghum, teff and yacon flours, using the Flash Profile method, a faster and less expensive method, when compared to the conventinal ones. Four formulations with different amounts of each flour were analyzed and the judges were asked to order the products in ascending order in relation to the intensity of each attribute under judgment. The data obtained were analyzed in the MATLAB R2018b software using the ComDim technique. The answers showed us that the panelists associate more positive attributes to the formulations with rice and sorghum flour and, as teff flour is added to the formulation, the tasters stop feeling the orange flavor and start to notice more the typical flavor of the flour. Thus, the objective of sensorially describing the formulations and obtaining answers that help in the adequacy of gluten-free orange cake formulations was fulfilled, in order to benefit the celiac public.